Metabolic and vascular risk factors are associated with reduced cerebral blood flow and poorer midlife memory performance. Issue 4 (25th October 2019) - MacIntosh, Bradley J.; Shirzadi, Zahra; Atwi, Sarah; Detre, John A.; Dolui, Sudipto; Bryan, Robert Nick; Launer, Lenore J.; Swardfager, Walter
Abstract: Midlife metabolic and vascular risk factors (MVRFs) predict cognitive decline and dementia; however, these risk factors tend to overlap, and the mechanisms underlying their effects on cognitive performance are not well understood. This cross‐sectional study investigates the contributions of MVRFs to regional cerebral blood flow (CBF) and verbal learning & memory among middle‐aged adults. We used partial least squares (PLS) analysis to create latent risk factor profiles and examine their associations to CBF in 93 regions of interest among 451 participants (age 50.3 ± 3.5 years) of the Coronary Artery Risk Development in Young Adults. This multivariate analysis revealed regional CBF was lower in relation to obesity (higher body mass index and waist circumference), dysregulated glucose homeostasis (higher fasting glucose, oral glucose tolerance, and higher fasting insulin), and adverse fasting lipid profile (lower high‐density lipoprotein cholesterol and higher triglycerides). In a sensitivity analysis, we found that significant associations between MVRFs and CBF were prominent in the hypertension‐medicated subgroup. In a mediation model, the PLS‐based MVRFs profile was associated with memory performance (rey auditory verbal learning test); however, CBF was not a significant mediator of this association. The results describe an adverse midlife metabolic profile that might set the stage for incipient dementia and contribute to widespread changes in CBF.